2023
DOI: 10.1177/03000605231173317
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with oxygen requirement and persistent symptoms 1 year after severe COVID-19 infection

Abstract: Objective We aimed to describe the prevalence and factors associated with the need for supplemental oxygen and persistent symptoms 1 year after severe SARS-CoV-2 infection. Methods In this historical cohort and nested case–control study, we included adults with severe COVID-19 (requiring admission to the intensive care unit or invasive mechanical ventilation). We evaluated factors associated with a need for supplemental oxygen and persistent symptoms 1 year after severe infection. Results We included 135 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…In Colombia, there have been two published reports on the presentation of post-COVID-19 conditions. Compared to these data, the obtained prevalence rate of dyspnea was more similar to that reported by Serrano et al, in which 31% of patients experienced dyspnea one year after ICU discharge (21). Anaya et al found a lower rate of this symptom in a sample of 100 patients with an antecedent of SARS-CoV-2 infection (22).…”
Section: Discussionsupporting
confidence: 85%
“…In Colombia, there have been two published reports on the presentation of post-COVID-19 conditions. Compared to these data, the obtained prevalence rate of dyspnea was more similar to that reported by Serrano et al, in which 31% of patients experienced dyspnea one year after ICU discharge (21). Anaya et al found a lower rate of this symptom in a sample of 100 patients with an antecedent of SARS-CoV-2 infection (22).…”
Section: Discussionsupporting
confidence: 85%